PELATIHAN PENULISAN ARTIKEL ILMIAH UNTUK GURU SEKOLAH DASAR DI GUGUS III MAMBEN LAUK KECAMATAN WANASABA - Sabahiyah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2021)
This training aims to improve teacher’s understanding of writing scientific articles at the Mamben lauk Cluster III Elementary School, Wanasaba District. This is based on their lack of understanding of scientific article writing so that they are difficult for the next promotion. This activity was attended by 22 teachers at the Mamben Lauk Cluster III Elementary School. The method of implementing this service activity is training with three stages of activites, namely the preparation stage, implementation stage and evaluation stage. The implementation of this community service activity includes providing material about writing articles and publishing articles in journals. In addition, the participants also practice writing scientific articles so that their mastery becomes more nature. The result obtained from this training activity are that the participants are very happy and enthusiastic about participating in this training activity because it can provide insight in the preparation of scientific articles which will later lead to an increase in their space class.